A study on bioactive constituents of Myrmecodia Platytyrea subsp. antoinii (Becc.) Huxley & Jebb / Nur Fadhilah Mohamad Haris - Mohamad Haris, Nur Fadhilah (2014)
The Myrmecodia genus (ant plant) is traditionally used to prevent and cure the cancer, heart problems and other serious diseases. Although there are many medicinal effects claimed, unfortunately there were only a few reports on the chemical isolation of the constituents on Myrmecodia platytyrea subsp. antoinii (Becc.) Huxley & Jebb. All the extracts from this plant were tested using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) method. The ethyl acetate (EA) extract was the most potent with the EC₅₀ value, 32.91 ± 2.23 |μg/mL. The potent extract in DPPH test was further fractionated using MPLC, which gave a total of 8 fractions (F1 - F8). All the fractions were tested using DPPH method and the F5 was the most potent with the EC₅₀ value, 21.57 ± 1.40 | μg/mL.The ferrous ion chelating (FIC) activity also was tested on EA extract and the result was negative…